AN OVERVIEW OF THE HUMAN BODY STRUCTURE AND CELLULAR COMPOSITION (Modern education and development, 2025)
The human body is a highly organized and complex system composed of various tissues, organs, and systems, all built from basic structural and functional units called cells. This article explores the general anatomical structure of the human body and provides an overview of the major types of cells, their functions, and roles in maintaining homeostasis. Understanding cellular and structural biology is essential for advancing medical science and health care.